An Investigation of the Referential Significance of Tradition in Contemporary Jewellery -- the Case of Han Dynasty Jade - Tian, Bingrui (Curtin University, 2020)
This study aims to learn from Han Chinese jade traditions, and to design contemporary jade carvings with Chinese traditional characters. This research sets up theoretical support for design principles and rules for contemporary jade carving. Through combination of exegesis and creative production, it proves that cultural refinement of traditional thought plays an active role in the cultural inheritance of contemporary jade design. It reinterprets the traditions and creates opportunities for the rebirth of these traditions.